Cognitive Impairment and Brain Reorganization in MS: Underlying Mechanisms and the Role of Neurorehabilitation - Nasios, Grigorios; Bakirtzis, Christos; Messinis, Lambros (Frontiers in Neurology, 2020)
Multiple sclerosis is a chronic, immune-mediated, inflammatory and degenerative disease of the central nervous system. Various mechanisms, mainly gray matter lesions, and brain atrophy, result in cognitive network dysfunction and can cause clinically significant cognitive impairment in roughly half the persons living with MS. Altered cognition is responsible for many negative aspects in patients’ lives, independently of physical disability, such as higher unemployment and divorce rates, reduced social activities and an overall decrease in quality of life. Despite its devastating impact it is not included in clinical ratings and decisions as it should. Only half the persons with MS exhibit cognitive dysfunction meaning that the other half remain cognitively intact. It appears that a dynamic balance between brain destruction and brain reorganization is taking place. This balance acts in favor of keeping brain systems functioning effectively, but not in all cases and not for ever. When these systems collapse, functional brain reorganization is not effective anymore and clinically apparent impairments are evident. It is therefore important to reveal which factors could make provision for the subpopulation of patients in whom cognitive impairment occurs. During the last few years a growing body of evidence has been accumulated, supporting the notion that cognitive rehabilitation and neuromodulation techniques such as transcranial magnetic or direct current stimulation improve cognitive performance in cognitively impaired patients with MS. In this Review we critically discuss the literature, focusing specifically on mechanisms of brain functional reorganization and practical issues for the application of neuromodulation procedures in clinical settings.